106 - EVALUATION ABOUT NEUROMOTOR PROFILE OF CHILDREN WITH QUADRIPLEGIC CEREBRAL PALSY. (Fiep Bulletin - online, 2011)
Abstract: The objective of this study was to evaluate the neuromotor development profile of 11 children of both gender from 3 to 5 years with cerebral palsy (CP), during a motor task. To ensure achievement of this study was used, the Gross Motor Function Classification System (GMFCS) in dimensions A (Lay and Roll) and B (Sitting). The children assessed in this study had a score ranging between 9.8 and 86.27 points, with a mean of 33.55 and a standard deviation of 1.9 and a coefficient of variation 68.95%. It can be concluded that the neuromotor profile of children 5 to 8 years old with cerebral palsy is deficient in relation to changes in the neurophysiologic mechanisms responsible for motor control.
Keywords: Evaluation; Children; Cerebral Palsy